2011
DOI: 10.1667/rr2431.1
|View full text |Cite
|
Sign up to set email alerts
|

Murine Prkdc Polymorphisms Impact DNA-PKcs Function

Abstract: Polymorphic variants of DNA repair genes can increase the carcinogenic potential of exposure to ionizing radiation. Two single nucleotide polymorphisms (SNPs) in Prkdc, the gene encoding the DNA-dependent protein kinase catalytic subunit (DNA-PKcs), have been identified in BALB/c mice and linked to reduced DNA-PKcs activity and mammary cancer susceptibility. We examined three additional mouse strains to better define the roles of the BALB/c Prkdc SNPs (R2140C and M3844V). One is a congenic strain (C.B6) that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…It should be mentioned that RLGS studies with mice numbering about 1,000 are not sufficient to indicate that BABL/c mice are more sensitive to radiation for mutation induction in spermatogonia. These results are in line with the results of studies at repair kinetics for radiation-induced DNA double-strand breaks (observed as cH2AX foci): namely, the kinetics were only slightly slower in BALB/c-derived cells compared with B6C3-derived cells (21).…”
Section: Possible Radiation Sensitivity Of the Balb/c Strainsupporting
confidence: 88%
“…It should be mentioned that RLGS studies with mice numbering about 1,000 are not sufficient to indicate that BABL/c mice are more sensitive to radiation for mutation induction in spermatogonia. These results are in line with the results of studies at repair kinetics for radiation-induced DNA double-strand breaks (observed as cH2AX foci): namely, the kinetics were only slightly slower in BALB/c-derived cells compared with B6C3-derived cells (21).…”
Section: Possible Radiation Sensitivity Of the Balb/c Strainsupporting
confidence: 88%
“…The presented results should be applicable in that analytical context when studying normal tissue effects of radiolabeled agents in tumor-bearing mice. In this context, it should be noted that reduced expression of the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and single nucleotide polymorphisms (SNPs) in Prkdc have been reported for several BALB/c strains which affected DNA repair proficiency upon ionizing radiation exposure [ 39 - 43 ]. To the best of our knowledge, the specific strain used in this study has not been categorized regarding DNA repair deficiency, but it is assumed that the genetic background exhibits similarly increased radiation sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous γH2AX foci of the Scid mice displayed in Fig. 5C may explain their susceptibility to mammary adenocarcinoma (49).…”
Section: Brca1 Promotes the Mre11-dependent Removal Of 5′ Adducts Frommentioning
confidence: 97%